Разработка методических рекомендаций по формированию инновационного предложения - Беляков, В.Н.; Шаровская, М.Н.; Хавер, В.Н. (Геотехническая механика, 2012)
Сформульовано визначення інноваційного проекту та інноваційної пропозиції, обґрунтовано форми реалізації інноваційних пропозицій, розглянуто зв’язок між формами реалізації інноваційних пропозицій та категоріями інноваційних проектів, розроблено рекомендації поформуванню інноваційних пропозицій різних форм реалізації. Definitions of the innovative project and innovative proposition are formulated; forms of implementation of innovative propositions are justified; the link between forms of implementation of innovative propositions and the categories of innovative projects is examined, the recommendations to create innovative propositions of various forms of implementation are developed.